Investigating the Effectiveness of Wattpad App on Students' Motivation in Reading - Ghaida Aisyah Putri; Nasrullah Nasrullah (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
Some students still find it challenging to be motivated to read. Internal and external factors can cause a lack of motivation to read. To motivate students to read, there are several reading platforms to use, one of them is Wattpad. Wattpad is a platform for reading and writing that was developed by Allen Lau and Ivan Yuen in 2006. There are many studies that use Wattpad as a media. However, those studies discuss the effect of the Wattpad app on reading comprehension, extensive reading, or writing ability. Only a few investigate the topic of reading motivation itself. Therefore, the researcher is interested in investigating the effectiveness of the Wattpad app on students' motivation to read. The objective of this research is to know the interplay of the Wattpad app to motivate students to read. This research uses a systematic literature review by collecting 20 journals taken from Google Scholar, ResearchGate, Microsoft Academic, and Science Direct. These journals are then sorted and analyzed to obtain data. The finding of this research is that Wattpad is an effective media to make students motivated to read.Keywords: Wattpad app, Motivation, reading